Hippocampal activity during memory and visual perception: The role of representational content. (December 2022) - Gardette, Jeremy; Cousin, Emilie; Bourgin, Jessica; Torlay, Laurent; Pichat, Cédric; Moreaud, Olivier; Hot, Pascal
Abstract: The functional organisation of the medial temporal lobe (MTL) has long been described on the basis of cognitive processes such as recollection or familiarity. However, this view has recently been challenged, and researchers have proposed decomposing cognitive phenomena into representations and operations . According to the representational view, representations, such as scenes for the hippocampus and objects for the perirhinal cortex, are critical in understanding the role of MTL regions in cognition. In the present study, 51 healthy young participants underwent functional magnetic resonance imaging (fMRI) while completing a visual-discrimination task. Subsequently, half of the participants performed a patch-cue recognition procedure in which "Rec" responses are believed to reflect the operation of pattern completion, whereas the other half performed a whole-item remember/know procedure. We replicated the previously-reported demonstration that hippocampal involvement in pattern completion is preferential for scenes as compared with objects. In contrast, the perirhinal cortex was more recruited for object processing than for scene processing. We further extended these results to the operations of strength-signal memory and visual discrimination. Finally, the modulation of hippocampal engagement in pattern completion by representational content was found to be specific to its anterior segment. This observation is consistent with the proposal that this segment would process broad/global representations, whereas the posterior hippocampus would perform sharp/local representations. Taken together, these results favour the representational view of MTL functional organisation, but support that this specialisation differs along the hippocampal long-axis.